2022
DOI: 10.1111/tid.13876
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating clinical effectiveness of SARS‐CoV‐2 vaccine in solid organ transplant recipients: A propensity score matched analysis

Abstract: Background: Solid organ transplant recipients (SOTRs) are at disproportionate risk for severe Coronavirus Disease 2019 . Vaccination is a key preventative strategy but is associated with decreased humoral responses among SOTR.Whether dampened immune responses correlate with reduced clinical effectiveness is unclear. Our study was designed to evaluate the clinical effectiveness of SARS-CoV-2 vaccination in the early vaccine era. Methods: We conducted a retrospective cohort study comparing SARS-CoV-2 infection r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, the most important and striking fndings were the protective efects of COVID-19 vaccination for hospitalization, overall mortality, and COVID-19-related mortality in this cohort. Our fndings are consistent with previous studies of the protective efect of vaccination in SOTRs [14][15][16][17]. Tese fndings reiterate the importance of vaccination against COVID-19 in kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 91%
“…However, the most important and striking fndings were the protective efects of COVID-19 vaccination for hospitalization, overall mortality, and COVID-19-related mortality in this cohort. Our fndings are consistent with previous studies of the protective efect of vaccination in SOTRs [14][15][16][17]. Tese fndings reiterate the importance of vaccination against COVID-19 in kidney transplant recipients.…”
Section: Discussionsupporting
confidence: 91%
“…Overall SOT vaccinated (with two doses of mRNA vaccine or one Ad26.Cov2.S dose) compared to unvaccinated SOT, the vaccine has shown to decrease COVID-19 incidence rate, risk of symptomatic COVID-19, critical disease and mortality [25,30,[44][45][46][47]. In contrast other studies reported that vaccination with one or two doses of m-RNA vaccine did not reduce risk of disease severity and death after SARS-CoV-2 infection in SOT recipients [48][49][50].…”
Section: One-two Doses Of Sars-cov-2 Vaccinementioning
confidence: 93%
“…Previous studies have shown that KTR have an inferior immune response to SARS-CoV-2 vaccination compared to the general population, and booster doses are necessary to enhance immune response for protection against SARS-CoV-2 infection and its severe complications [ 4 , 11 ]. However, the real-world efficacy of booster vaccinations in KTR, especially in Eastern countries with differing vaccine distribution and socioeconomic factors from Western countries, still require more data [ 9 , [11] , [12] , [13] , [14] , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, most of the information about COVID-19 outcomes in KTR comes from Western countries [ [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. This leaves a notable gap in knowledge about Asian KTR, where a wider variety of vaccine types, including inactivated, viral vector, and mRNA vaccines, have been used.…”
Section: Introductionmentioning
confidence: 99%